BIOBRIKET DARI CAMPURAN LIMBAH KULIT BIJI METE, SEKAM DAN JERAMI SERTA BUNGKIL JARAK, SEKAM DAN JERAMI - Faleh Setia Budi; Luqman Buchori (Diponegoro University, 2013)
The petroleum is the fuel derived from fossil which can not be renewable and the deposit in the earth is not morenow. In the middle 2008, the price of petroleum achieved US 147/Barrel because the supply of petroleum toworld market was reduced. This situation forced the appearance of the alternative energy which can replace thefossil fuel in the future. Their result of combustion has low emission so that they can be reduced the pollutionand were environment friendly. Biobriquette is the one alternative energy which expected to be able to replacethe kerosene and LPG. This research aims to get the exactly composition and type in manufacturing ofbiobriquette from cashew nut shell and jatropa shell waste. The variables choose as the independence variablewas the type of waste (cashew nut shell and jatropa shell) and the compositions (40, 60, 80 and 100%). Theothers are the fixed variable such as the size of briquette 4 cm and the total weight/biquette 25 g. The responseor parameters observed in the experiment were the color, the value of calor, the length of combustion and thecolor of fire. The result of experiment showed that composition of the material greatly affected the quality ofbriquette produced. The composition 100% owns the highest calor of combustion. The calor of Jatropa wastewas higher than that of cashew nut shell.